OPTIMASI FORMULA SERTA KARAKTERISASI KIMIA DAN SENSORIS PADA PRODUKSI FRUIT LEATHER CARICA (Carica pubescens L.) - Astuti, Santi Dwi; Ayuningtyas, Laksmi Putri; Prihananto, V.; Dewi, Ervina Mela; Ferliana, Agnes (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
The added value of carica fruit can be increased by using overripe fruit to make processed products. One such product with great potential is fruit leather. This study aims to determine the optimal proportions of high fructose syrup (HFS) and sorbitol for producing carica fruit leather products that are highly desirable, and to compare the chemical characteristics of these products with those of the control product (without the addition of HFS and sorbitol). The study employed the Response Surface Methodology (RSM) with a Central Composite Design (CCD) experimental design, consisting of two factors and two blocks, to generate 14 treatment combinations. The research data were analysed using the Design-Expert V.10 application. Then, the data analysis of the optimum product and the control product was carried out using a T-test at a 95% confidence level with the IBM SPSS Statistics 25 application. The results of this study are an optimum formula for carica fruit, obtained from a proportion of 7.13% HFS and 2.31% sorbitol, with a desirability value of 0.65. Compared to the control product, the optimum product has a lower Aw value and ash content, but a higher fat, total dietary fibre, carbohydrate, total sugar and vitamin C content.